1995
DOI: 10.1192/bjp.167.3.307
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Sexual Dysfunctions by Sex Therapy and Other Approaches

Abstract: Sex therapy is now a well-established form of treatment. It should be more widely available for patients seen in psychiatry departments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 40 publications
1
37
0
2
Order By: Relevance
“…As noted in the introduction to this section, our application of EST criteria may have led to an underestimated efficacy for the less recently developed and investigated treatments. In fact, Hawton and Catalan (1986) and Hawton (1995) have suggested that the paucity of controlled studies of earlier treatments does not necessarily imply that they are not efficacious. For example, they reported an overall improvement rate of 66% for patients in the Masters and Johnson program and stated that they consider it a treatment that is now "wellestablished" (Hawton, 1995, p. 307).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As noted in the introduction to this section, our application of EST criteria may have led to an underestimated efficacy for the less recently developed and investigated treatments. In fact, Hawton and Catalan (1986) and Hawton (1995) have suggested that the paucity of controlled studies of earlier treatments does not necessarily imply that they are not efficacious. For example, they reported an overall improvement rate of 66% for patients in the Masters and Johnson program and stated that they consider it a treatment that is now "wellestablished" (Hawton, 1995, p. 307).…”
Section: Discussionmentioning
confidence: 99%
“…Because the more comprehensive therapies have been studied more recently and according to recent experimental design expectations, evidence for the efficacy of comprehensive treatments of HSDD is more likely to exist than for the early treatments of orgasmic disorders developed by Masters and Johnson and LoPiccolo and Lobitz. In other words, the efficacy status reported in the following section may be an underestimate of the persuasiveness of the evidence, especially regarding early treatments for sexual dysfunctions (see other reviews by Beck, 1995;Emmelkamp, 1994;Hawton, 1995;LoPiccolo & Stock, 1986).…”
Section: Sexual Dysfunctionsmentioning
confidence: 99%
See 2 more Smart Citations
“…An emphasis on brevity of treatment is one of the characteristics of modern sex therapy: Hawton (1995) suggests that 'standard sex therapy', which has been strongly influenced by the work of Masters and Johnson (1970), consists on average of between 8 and 20 sessions delivered over a period of 3 to 9 months. The intensive, dyadic and predominantly behavioural approach to treating sexual symptoms outlined by Masters and Johnson (1970) marked a significant shift from the longer-term psychotherapy for sexual problems, which characterised its psychodynamic predecessors.…”
Section: Introductionmentioning
confidence: 99%